Science education research in Brazil: Historical aspects, researchers' representations, and the state of the art - de Almeida, Maria José P. M.; Nardi, Roberto [UNESP] (My University, 2020)
In this chapter, we describe some aspects of science education research in Brazil, highlighting historical aspects, researchers' representations and the state of art of this area of study. We adopted the position of Science Education researchers who, for many years, have witnessed the constitution, growth and consolidation of this area as an investigation field. From this viewpoint, it is clear to us that this constitution did not occur in the same way, or attained the same degree of growth in different Latin American countries, and we cannot even say that it is equally disseminated in different regions of a country. In turn, it is not our intention to speak in the name of a block of countries, the total area of which exceeds 20 million square kilometers, and in which more than 600 million inhabitants live. We would like to stress, also, the relevance that a detailed survey of events, institutions, research groups and journals in each of the countries of the block would have for the Science Education field. A complete record of this memory would not only contribute to acknowledging the relevance of all that has been done, but could also increment the large number of interactions already existing in the region. A study like that is a desirable and huge task. However, the intention here is merely to highlight some factors that may somehow justify such a study. For this, we concentrate on Brazilian institutions, events and journals, Regarding which we count on a larger amount of information. We thus intend to exemplify some of the factors associated to the origins, growth and consolidation of the Science Education area in Brazil.
Keywords: Science education in Brazil; Science education research in Brazil; Science education research memories